2021
DOI: 10.1080/14735903.2021.1975437
|View full text |Cite
|
Sign up to set email alerts
|

Continuing cereals research for sustainable health and well-being

Abstract: Cereals research over the past fifty years has led to huge improvements in production, productivity and food security. The current emphasis in agri-nutrition on micronutrients has cast doubt on the need to continue to invest in cereals. However, besides the essential dietary energy content of cereals such as wheat, maize and rice, we argue that there are two important factors to consider. First, the intrinsic micronutrient content of cereals is not often taken into account. As a major dietary component, cereal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…White et al (2020) revealed that exposure to green or blue spaces may effectively reduce mental and depression problems to benefit the achievement of SDG 3. Poole et al (2022) presented the advantages of cereals and acknowledged that they are a rich source of both dietary fiber and a range of bioactive food elements essential for meeting SDG 3. Vogt et al (2022) explored the changes in meeting SDG 3 by investigating veterans' health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…White et al (2020) revealed that exposure to green or blue spaces may effectively reduce mental and depression problems to benefit the achievement of SDG 3. Poole et al (2022) presented the advantages of cereals and acknowledged that they are a rich source of both dietary fiber and a range of bioactive food elements essential for meeting SDG 3. Vogt et al (2022) explored the changes in meeting SDG 3 by investigating veterans' health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Linked to the wider food system, a multidisciplinary and multisectoral approach is necessary in Afghanistan to encompass the downstream value chain issues in intermediary small to medium enterprise development (the missing or hidden middle of enterprise of Reardon, 2015 andAlibhai et al, 2017). The concept of an integrated, multidisciplinary wheat food system has recently been described, specifically highlighting the need for synthesis and alignment across agroindustries and the political economy and through to consumer science (Poole et al, 2021). with seed multiplication programmes connected to local farming systems and incorporating testing and quality control and external support to develop a coherent Afghan seeds programme.…”
Section: The Necessity Of a Multisectoral Approach To Wheat Improvementmentioning
confidence: 99%
“…Globally, wheat ( Triticum aestivum L.) breeding efforts over the past 70 yr have significantly increased grain yield potential as well as resistance to abiotic and biotic stresses (Poole et al., 2021). Wheat products are an important component of human diets globally; whole grain wheat products consumed in South Asia and Ethiopia provide essential micronutrients such as iron (Fe) and zinc (Zn), in addition to dietary energy and protein.…”
Section: Introductionmentioning
confidence: 99%